Pengaruh Kemampuan Manajemen dan Motivasi Kepala Sekolah terhadap Kinerja Guru Sekolah Dasar di Kecamatan Rambutan - Desi Rahmawati; Syarwani Ahmad; Djunaidi Djunaidi (Departement of Mathematics Education, 2025)
This study aims to determine and analyze: (1) The influence of the principal's managerial ability on teacher performance; (2) The influence of the principal's motivation on teacher performance; (3) The influence of the principal's managerial ability and motivation together on teacher performance. This study is a quantitative study with a correlation method. This study was conducted at an elementary school in Rambutan District with 42 teachers as respondents. The data collection technique used a questionnaire. The validity test used the product moment formula while the reliability test used Cronbach's Alpha. The analysis prerequisite test used the normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, and the data was analyzed using multiple regression analysis techniques. The results of the study showed that: (1) there was an influence between the principal's managerial ability on teacher performance of 10.5%; (2) there was an influence between the principal's motivation on teacher performance of 48.8%; (3) there was an influence between the principal's managerial ability and motivation on teacher performance of 46.1%.